-6n+10=4-8n

Simple and best practice solution for -6n+10=4-8n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6n+10=4-8n equation:


Simplifying
-6n + 10 = 4 + -8n

Reorder the terms:
10 + -6n = 4 + -8n

Solving
10 + -6n = 4 + -8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8n' to each side of the equation.
10 + -6n + 8n = 4 + -8n + 8n

Combine like terms: -6n + 8n = 2n
10 + 2n = 4 + -8n + 8n

Combine like terms: -8n + 8n = 0
10 + 2n = 4 + 0
10 + 2n = 4

Add '-10' to each side of the equation.
10 + -10 + 2n = 4 + -10

Combine like terms: 10 + -10 = 0
0 + 2n = 4 + -10
2n = 4 + -10

Combine like terms: 4 + -10 = -6
2n = -6

Divide each side by '2'.
n = -3

Simplifying
n = -3

See similar equations:

| 10c=2+8c | | 3(b+3)+4(b+2)+b=89 | | 11=-3+z | | 24x+4=19x+4 | | 3x-(4x+6)=x-9 | | 11=-4.9t^2+120t | | 10x^2+12x-1=4x | | 8-(5/7)x-32 | | 2w+3(w+2)+2(w+5)=44 | | -10+k=10-9k | | -9j+10=10j | | -4a+16+6a=-9a | | (7x+3)(x-5)=-2x(5x+6)+x-19 | | -6-7f=-6f | | X-27=84 | | t-10=10-9t | | 2+7cosx=4sin^2x | | 12x+14=134 | | y+2(y+3)+3(y+1)=45 | | 4p-7.3=16.7 | | 8-2w=-w | | -6n=-6-7n | | 8r+10=9r | | 1/5n=-8 | | 2r+3(r+3)+3r=1 | | x^2+18x+73=-9 | | y=-4.9t^2+120t | | 270=920(1-d) | | 8.7=3.5m-3.5(5.4-6m) | | 4a+5(a+3)+-14=64 | | -10-3p=10-5p-8 | | 4m^2n-6n^2-2mn= |

Equations solver categories